The SAGE handbook of counselling and psychotherapy - Feltham, Colin; Hanley, Terry; Winter, Laura Anne
"This edition brings together comprehensively the fundamentals of counselling and psychotherapy for both trainees and experienced practitioners seeking expansion of their knowledge base. Focuses on the British society and multicultural profile for counseling and psychotherapy. This book tries to draw together as much consensual information, practice wisdom, mainstream theory, and pertinently challenging material as possible."--Provided by publisher.